Determination of better insulating oil for power transformer oil application using Analytical Hierarchy Process (AHP) - Arief, Yanuar Z.; Abd Hamid, Nazirah; Izzwan Saad, Mohd Hafiez; Al Hakim, Rosyid R (Journal of Global Engineering Research and Science, 2022)
The Analytical Hierarchy Process (AHP) which was developed by Saaty is a decision-making tool in the year of 1970s. The system is able to solve the complex analysis which could not be performed by the human brain. In this project, the AHP system is chosen to select a better insulating oil for power transformer oil application since the insulation is the most important part of a transformer. In this research method based on the AHP technique, there are six criteria are involved in the model, namely breakdown voltage, dissipation factor/tan delta, pour point, kinematic viscosity, density, and flash point. While, the given alternatives are palm oil, canola oil, palm fatty acid ester (PFAE) oil, corn oil, sunflower oil, and soybean oil, respectively. A spreadsheet software application (Microsoft Excel) was employed in this study. As the result, it is found that the PFAE oil is the best insulating oil that able to be used in a real power transformer oil application. All requirements as insulating oil for transformer oil of PFAE oil are met significantly.